Recomendações para Análise Mutacional em Tumores do Estroma Gastrointestinal (GISTs): Grupo de Trabalho Português GIST – Proposta de Condeixa - Lopes, JM (2012)
The authors outline recommendations for the mutational analysis of GISTs unanimously approved by a multidisciplinary group on July 20th, 2012. The mutational status of KIT and PDGFRA allows identifying therapeutic targets to tyrosine kinase inhibitors (TKIs), and therefore, the safe clinical practice in the biotherapy decisions for patients with GISTs should include the analysis of the mutational status. The mutational analysis of the primary disease is not recommended in the diagnostic routine of most GISTs; nevertheless may have prognostic value and be useful in the selection for adjuvant treatment after complete resection of primary GIST, and is considered experimental in the progressive disease under treatment with TKIs. The mutational analysis should be considered in selected cases as described herewith and performed in laboratories in compliance with high standards of quality assurance, considering the strong impact on clinical decisions.Os autores apresentam as recomendações para a análise mutacional de GISTs, aprovadas por unanimidade por um grupo multidisciplinar em 20 de Julho de 2012. O estado mutacional de genes como o KIT e o PDGFRA permite identificar alvos terapêuticos para inibidores da tirosinacínase (ITKs) e, por isso, a boa prática clínica nas decisões bioterapêuticas de doentes com GISTs deve incluir a análise do estado mutacional. A análise mutacional da doença primária não é recomendada na rotina diagnóstica da generalidade dos GISTs; no entanto, pode ter valor prognóstico e ser útil na seleção de doentes, após ressecção completa de GIST primário e é considerada experimental na doença progressiva sob tratamento com ITKs. A análise mutacional deve considerar-se nos casos selecionados descritos neste texto e ser realizada em laboratórios em conformidade com padrões elevados de garantia de qualidade, atendendo ao seu elevado impacto sobre as decisões clínicas.